2009
DOI: 10.1634/theoncologist.2009-0057
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Outcomes Analysis of Palliative Procedures Performed for Malignant Intestinal Obstruction Due to Recurrent Ovarian Cancer

Abstract: Objective. To obtain prospective outcomes data on patients (pts) undergoing palliative operative or endoscopic procedures for malignant bowel obstruction due to recurrent ovarian cancer.Methods. An institutional study was conducted from July 2002 to July 2003 to prospectively identify pts who underwent an operative or endoscopic procedure to palliate the symptoms of advanced cancer. This report focuses on pts with malignant bowel obstruction due to recurrent ovarian cancer. Procedures performed with an upper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 9 publications
3
43
1
1
Order By: Relevance
“…In the present study, significantly longer survival following the diagnosis of MBO in the operative than the non-operative group was observed, in accordance with several previous studies (3,10,11). By comparing the characteristics of the two groups, the performance status at diagnosis of MBO was found to be superior in the operative group as expected, since surgery had been considered only for patients with a relatively good performance status, unsurprisingly leading to the longer survival in the operative group.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, significantly longer survival following the diagnosis of MBO in the operative than the non-operative group was observed, in accordance with several previous studies (3,10,11). By comparing the characteristics of the two groups, the performance status at diagnosis of MBO was found to be superior in the operative group as expected, since surgery had been considered only for patients with a relatively good performance status, unsurprisingly leading to the longer survival in the operative group.…”
Section: Discussionsupporting
confidence: 91%
“…Surgery for malignant bowel obstruction is controversial, given the high mortality and morbidity and the low post-operative median survival. In a review of 700 surgeries for malignant bowel obstruction in ovarian cancer patients, the rate of major morbidity was 32%, and the median survival was 17 weeks [34]. In addition, 50% of patients either died or had a recurrence of symptoms within 90 days of surgery.…”
Section: Malignant Bowel Obstructionmentioning
confidence: 99%
“…Surgical strategy is determined upon intraoperative findings, and no standard guidelines are available. Several studies demonstrated benefits in symptoms relief with resumption of oral intake after palliative surgery for malignant bowel obstruction in 32-100 % of patients [60][61][62][63][64][65][66]. QoL measures are not reported by any available study.…”
Section: Palliative Surgery and Managing Bowel Obstruction In Peritonmentioning
confidence: 99%
“…A frequent complication, occurring in from 6 % to 47 % of patients, is reobstruction [61-63, 66, 69]. Furthermore, duration of symptom relief may be short [66,69] and hospital stay considerable in relation to patients life expectancy, which ranges from 1 to 94 days [70]. When obstructive symptom resolution is achieved and is long lasting, survival advantage may be significant, rising from 26 to 36 days to 154 to 192 days in some series [62,71].…”
Section: Palliative Surgery and Managing Bowel Obstruction In Peritonmentioning
confidence: 99%